(untitled) (Global Journal of Science Frontier Research, 2023)
The purpose of this work was to estimate heavy element bioaccumulation in four staple food crops species, specifically sweet cassava (Manihot esculenta), maize (Zea mays L.), plantain (Musa paradisiaca L.), and white yam (Dioscorea rotundata L.), and to assess the human health risks of food crops intake. The analyzed heavy elements included arsenic, cadmium, copper, manganese, lead, and zinc for their bioaccumulation factors to provide benchmark point information regarding ecological health and the suitableness of a farm established in the time ahead. The bioaccumulation factor, heavy elementpollution load index, acceptable daily intake of elements, human health risk index, target hazard quotient toxicology, total diet target hazard quotient, and total target hazard quotienttechniques were employed to estimate the human health risks analysis caused by heavy elements via staple food crops consumption. Quality control techniques comprised blank analysis, spike recovery analysis, and calibration of concentrations. We adopted descriptive and inferential statistics to analyze the data. Overall mean HEPLI values for both seasons were 0.54 and 0.88, 0.28 and 0.92, 0.31 and 0.37, 0.52 and 0.55, 0.28 and 0.55 and 0.24 and 0.31, for As, Cd, Cu, Mn, Pb, and Zn, respectively. Elements in staple food crops were lower than in soils, with ranges of 1. for As, Cd, Cu, Mn, Pb, and Zn, respectively.